2016
DOI: 10.1037/pst0000024
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of experiential dynamic therapy for psychiatric conditions: A meta-analysis of randomized controlled trials.

Abstract: Experiential dynamic therapy (EDT) is a subgroup of short-term psychodynamic psychotherapy (STPP) that emphasizes patients' in-session affective processing. To evaluate the efficacy of EDT for psychiatric conditions, we conducted a meta-analysis of randomized controlled trials. Twenty-eight studies published between 1978 and 2014 were included, encompassing 1,782 adult patients with mood, anxiety, personality, or mixed disorders. Across targeted outcome domains, medium-size between-groups effects (Cohen's ds r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 100 publications
(117 reference statements)
2
34
0
Order By: Relevance
“…Treatment implications may differ for socially anhedonic individuals depending on the personality traits that are most salient. Individuals with social anhedonia, operationally defined by low ACIPS scores, may benefit from cognitive-behavioral treatments that emphasize social skills training ( Granholm et al, 2014 ) and/or experiential therapy ( Osimo, 2003 ; Lilliengren et al, 2016 ). Individuals with social anhedonia, operationally defined by high RSAS scores, may benefit most from treatments that emphasize behavioral activation training ( Dimidjian et al, 2011 ; Hershenberg et al, 2015 ), and/or motivational interviewing ( Miller and Rollnick, 2013 ; Romano and Peters, 2016 ).…”
Section: Limitations Strengths and Future Directionsmentioning
confidence: 99%
“…Treatment implications may differ for socially anhedonic individuals depending on the personality traits that are most salient. Individuals with social anhedonia, operationally defined by low ACIPS scores, may benefit from cognitive-behavioral treatments that emphasize social skills training ( Granholm et al, 2014 ) and/or experiential therapy ( Osimo, 2003 ; Lilliengren et al, 2016 ). Individuals with social anhedonia, operationally defined by high RSAS scores, may benefit most from treatments that emphasize behavioral activation training ( Dimidjian et al, 2011 ; Hershenberg et al, 2015 ), and/or motivational interviewing ( Miller and Rollnick, 2013 ; Romano and Peters, 2016 ).…”
Section: Limitations Strengths and Future Directionsmentioning
confidence: 99%
“…Evidence for the efficacy of approaches within the psychoanalytic tradition is accumulating (e.g., Fonagy, ; Leichsenring, Kruse & Rabung, ; Lilliengren, Johansson, Lindqvist, Mechler, & Anderson, ; Shedler, ; Yakeley, ). Findings from RCTs document that psychoanalytic approaches work for most people on average for a variety of presenting concerns, including depression, anxiety, somatic problems, substance‐related disorders, and personality disorders (Fonagy, ; Leichsenring et al, ; Lilliengren et al, ; Shedler, ; Yakeley, ). Yet, the notion that treatment “work(s) for most people on average” distinguishes RCTs from person‐centered analyses that seek to discern “subgroups of individuals who respond very well to treatment and subgroups who do not respond well” (Frankfurt et al, , p. 623).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we aim to evaluate the clinical‐ and cost‐effectiveness of Intensive Short‐Term Dynamic Psychotherapy (ISTDP; Davanloo, , ; Abbass, ) for patients with GAD. ISTDP is an emotion‐focused, experiential psychodynamic treatment model with a growing evidence base (Abbass, Town, & Driessen, ; Lilliengren, Johansson, Lindqvist, Mechler, & Andersson, ; Town & Driessen, ). Previous studies have indicated that ISTDP may be effective in complex psychiatric conditions, such as personality disorders (e.g., Abbass, Sheldon, Gyra, & Kalpin, ; Solbakken & Abbass, ), treatment resistant depression (Town, Abbass, Stride, & Bernier, ) and medically unexplained symptoms (Abbass et al, ; Chavooshi, Mohammadkhani, & Dolatshahee, ), all of which overlap considerably with GAD.…”
Section: Introductionmentioning
confidence: 99%